2016
DOI: 10.17795/jjhs-36192
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat Stress on Job Satisfaction, Job Performance and Occupational Stress in Casting Workers

Abstract: Background: Job satisfaction, job performance, job stress and heat stress affect the productivity of workers. Objectives: This research aimed to study the relationship between heat stress indices with job satisfaction, job performance and job stress in casting workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Undoubtedly, feelings of discontentment can arise from unproductive settings and reduce satisfaction within the working environment. Workers perceived heat to impact job satisfaction on a daily or weekly basis, congruent with other studies conducted in hot occupational settings (Dawal and Taha, 2006;Dehghan et al, 2016;Dianat et al, 2016). Further, a total of 30 workers reported between 63 and 89 days of sick leave due to heat-related illness, while only 15 workers sought medical attention.…”
Section: Negative Impacts Within Workplace Settingssupporting
confidence: 80%
“…Undoubtedly, feelings of discontentment can arise from unproductive settings and reduce satisfaction within the working environment. Workers perceived heat to impact job satisfaction on a daily or weekly basis, congruent with other studies conducted in hot occupational settings (Dawal and Taha, 2006;Dehghan et al, 2016;Dianat et al, 2016). Further, a total of 30 workers reported between 63 and 89 days of sick leave due to heat-related illness, while only 15 workers sought medical attention.…”
Section: Negative Impacts Within Workplace Settingssupporting
confidence: 80%
“…Additional potential disturbing factors to be analyzed are the weather conditions; this is due to the particular market on construction increasing demand of rebars. However, high temperature stress [59] has significance for on the job satisfaction, performance and indirectly on environmental behavior.…”
Section: Manufacturing Casementioning
confidence: 99%
“…The obtained results suggested that heat has an impact on job performance but has no significant impact on job satisfaction and occupational stress. 5 The insignificant results for job satisfaction and occupational stress by the dentists may be because they were scared of losing their jobs. This is in accordance with a study conducted by Kobza J et al and Pandita V et al where the dentists where reasonably satisfied with their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…4 A hot environment is a kind of unhealthy environment and in the recent years its psychological effects on workers have increased. 5 Such unhealthy environment can be responsible for the occupational stress, weak performance and job dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation